2007
DOI: 10.1128/aem.01064-07
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of γ-Aminobutyric Acid by Lactic Acid Bacteria Isolated from a Variety of Italian Cheeses

Abstract: The concentrations of ␥-aminobutyric acid (GABA) in 22 Italian cheese varieties that differ in several technological traits markedly varied from 0.26 to 391 mg kg ؊1 . Presumptive lactic acid bacteria were isolated from each cheese variety (total of 440 isolates) and screened for the capacity to synthesize GABA. Only 61 isolates showed this activity and were identified by partial sequencing of the 16S rRNA gene. Twelve species were found. Lactobacillus paracasei PF6, Lactobacillus delbrueckii subsp. bulgaricus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
303
1
2

Year Published

2014
2014
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 387 publications
(310 citation statements)
references
References 52 publications
(53 reference statements)
4
303
1
2
Order By: Relevance
“…GABA is present in small quantities in many plant sources, vegetables, for example spinach, potatoes, cabbage asparagus (broccoli), tomatoes, fruits, for example apples, grapes, in cereals, for example barley, maize. The increased amount is found mainly in fermented products, especially fermented dairy products, soy sauce (Yamakoshi et al, 2007), cheeses (Siragusa et al, 2007) and so on. Natural addition of GABA is in high demand over the addition of chemical nutrient GABA since consumers prefer naturally occurring substances and the fermentation helps to reduce the cost of the foods due to the omission of chemical addition of GABA and also provides attractive foods with better taste and at the same time replaces the chemical GABA by natural GABA .…”
Section: Resultsmentioning
confidence: 99%
“…GABA is present in small quantities in many plant sources, vegetables, for example spinach, potatoes, cabbage asparagus (broccoli), tomatoes, fruits, for example apples, grapes, in cereals, for example barley, maize. The increased amount is found mainly in fermented products, especially fermented dairy products, soy sauce (Yamakoshi et al, 2007), cheeses (Siragusa et al, 2007) and so on. Natural addition of GABA is in high demand over the addition of chemical nutrient GABA since consumers prefer naturally occurring substances and the fermentation helps to reduce the cost of the foods due to the omission of chemical addition of GABA and also provides attractive foods with better taste and at the same time replaces the chemical GABA by natural GABA .…”
Section: Resultsmentioning
confidence: 99%
“…The GAD produced by L. brevis was biochemically well characterized previously (Hiraga et al, 2008). L. brevis PM17 was also reported for the GABA-producing ability (Siragusa et al, 2007).…”
Section: Bacterial Identificationmentioning
confidence: 99%
“…delbrueckii subsp. bulgaricus (Siragusa et al, 2007), Bifidobacterium dentium (Barrett et al, 2012), and Streptococcus salivarius subsp. thermophilus (Yang et al, 2008b) are reported to produce GAD with different efficiency and optimum conditions.…”
Section: Screening and Kinetics Of Gad Activitymentioning
confidence: 99%
See 1 more Smart Citation
“…Concentration of individual FAAs in cheese was determined as described by Siragusa et al (2007), with few modifications. In detail, 30 g of cheese was grated and homogenised (5 min treatment) with 90 mL of 50 mmol L À1 phosphate buffer, pH 7.0, in a blender.…”
Section: Determination Of Ph Water Activity and Free Amino Acids Inmentioning
confidence: 99%